NON PERFORMING FINANCING, RETURN ON ASSET, CAPITAL ADEQUACY RATIO DAN DANA PIHAK KETIGA YANG MEMPENGARUHI PEMBIAYAAN MUDHARABAH PADA BANK UMUM SYARIAH DI INDONESIA - Siti Rohqimah, 13.05.52.0056; Puspitasari, Elen (Students Journal of Accounting and Banking, 2017)
The purpose of this study is to examine and analyze the influence from non-performing financing, return on assets, capital adequacy ratio, third party funds on mudharabah financing at Shari`s Commercial Bank. The type of data used in this study is secondary data, the data in this study obtained from the Financial Report and Annual Report 2012-2016. Sampling method used is purposive sampling. The amount of data processed by 32 Syariah Commercial Banks. Methods of data analysis using multiple linear regression. The results showed that non-performing financing, and capital adequacy ratio had a negative and significant effect on mudharabah financing, while third party fund variable had a positive and significant influence on mudharabah financing. For return on asset variable has no effect on mudharabah financing. Keywords:Â Mudharabah Financing, Non Performing Financing, Return on Assets, Capital Adequacy Ratio, and Third Party Funds